Super Dosing of IP6 Phytase in Phosphorus-Deficit Diets to Replace Added Phosphorus and Evaluate Growth Performance, Nutrient Digestibility and Bone Mineralization of Broiler Chickens - Bahadur Ali; Muhammad Irfan (Journal of Global Innovations in Agricultural Sciences)
Phosphorus in phytate is poorly available to monogastric animals due to their lack of the phytase enzyme, leading to increased phosphorus excretion and environmental pollution. Additionally, broiler diets high in phytate and low in available phosphorus negatively affect growth performance, nutrient absorption, and bone mineralization. This study was planned to evaluate the effect of adding IP6 phytase as a dietary replacement of added phosphorus with generic phosphorus in broiler diets on growth performance, nutrient digestibility, and bone mineralization. Seven hundred and fourteen (714) day-old Ross-308 broiler chicks were randomly distributed into forty-two experimental pens (6 replicates and 17 birds/pen). Seven isonitrogenous experimental diets were formulated for starter (1-21 days) and finisher (22-28 days) phases. The first diet was served as control (C), formulated following nutrient recommendations for Ross® broilers. Three negative control diets were formulated with available phosphorus levels of 0.15%, 0.18%, and 0.21%, each supplemented with phytase at 1000 FTU/kg and 2000 FTU/kg across both phases. Phytase supplementation increased the body weight gain during days 01-07 (p=0.01), 08-14 (p=0.004), 15-21 (p=0.0001), 22-28 (p=0.036) and 0-28 (p<0.001). Feed intake was not significantly affected during days 01-07 (p=0.114) and 08-14 (0.094). However, higher levels of phytase (2000 FTU/kg with 0.21% Av. P) increased feed intake during days 15-21 (0.037) while a decrease in feed intake was observed during days 22-28 (0.009). Increased level of phytase (2000 FTU/kg) also improved the digestibility of dry matter (p=0.049), crude protein (p=0.03), and ether extract (p=0.026). Further, bone mineralization improved with the addition of phytase in the broiler diet. In conclusion, phytase supplementation can replace added phosphorus by releasing bound phosphorus from phytate without compromising the growth performance, nutrient digestibility, and tibia mineral content in broilers.